2014
DOI: 10.1270/jsbbs.63.483
|View full text |Cite
|
Sign up to set email alerts
|

QTL pyramiding for improving of cold tolerance at fertilization stage in rice

Abstract: Vigorous cold tolerance at the fertilization stage (CTF) is a very important characteristic for stable rice production in cold temperature conditions. Because CTF is a quantitatively inherited trait, pyramiding quantitative trait loci (QTLs) using marker-assisted selection (MAS) is effective for improving CTF levels in rice breeding programs. We previously identified three QTLs controlling CTF, qCTF7, qCTF8 and qCTF12, using backcrossed inbred lines derived from a cross between rice cultivar Eikei88223 (vigoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Recently, Najeeb et al (2019) reviewed the LTS tolerance QTLs reported in rice at germination and seedling and booting stages while using different genetic backgrounds such as DHs, RIL S , BILs, BC 2 F 1 , F 2 , and F 8 as mapping populations. Among these populations, a few major QTLs have been identified by Andaya and Mackill (2003b), Fujino et al (2004), Lou et al (2007), Baruah et al (2009), Shinada et al (2014), Fig. 4 Depicted representation of the distribution pattern of lowtemperature stress (LTS) tolerance QTLs associated with phenotypic traits on 12 chromosomes, The total phenotypic variance explained (PVE) of different QTL indicates in the middle part with black color font, and percentage of number QTLs (%) distributed on 12 chromosomes were shown at the outter boundary of pie chart (Chr = chromosome; PVE = phenotypic variation explained; LTG = low-temperature germination; LTGS = low-temperature germination stress index; BMSI = biomass stress index; SL = shoot length; RL = root length; SLSI = shoot length stress index; RLSI = root length stress index; SGI = shoot growth index; SVI = seedling vigor index) Jiang et al (2017), andShakiba et al (2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Najeeb et al (2019) reviewed the LTS tolerance QTLs reported in rice at germination and seedling and booting stages while using different genetic backgrounds such as DHs, RIL S , BILs, BC 2 F 1 , F 2 , and F 8 as mapping populations. Among these populations, a few major QTLs have been identified by Andaya and Mackill (2003b), Fujino et al (2004), Lou et al (2007), Baruah et al (2009), Shinada et al (2014), Fig. 4 Depicted representation of the distribution pattern of lowtemperature stress (LTS) tolerance QTLs associated with phenotypic traits on 12 chromosomes, The total phenotypic variance explained (PVE) of different QTL indicates in the middle part with black color font, and percentage of number QTLs (%) distributed on 12 chromosomes were shown at the outter boundary of pie chart (Chr = chromosome; PVE = phenotypic variation explained; LTG = low-temperature germination; LTGS = low-temperature germination stress index; BMSI = biomass stress index; SL = shoot length; RL = root length; SLSI = shoot length stress index; RLSI = root length stress index; SGI = shoot growth index; SVI = seedling vigor index) Jiang et al (2017), andShakiba et al (2017).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a few M-QTLs with relatively higher PV explained were consistently governing two stages, such as LTGS(II) and LTGS(III) (20.70 Mb) on chromosome 1 and LTGS(II) and LTGS(III) on chromosome 3. In earlier reports, Fujino et al (2008), Li et al (2013), Cui et al (2013), Shinada et al (2014), and Zhu et al (2015) mentioned a few stable QTLs across several environments under LTS. The importance of stable QTLs is that they have larger additive effects and are less affected by the environment.…”
Section: Phenotypic and Genotypic Variation Of Lts Tolerance Traitsmentioning
confidence: 92%
“…They identified three QTLs for CTF and a clear effect by QTL, qCTF7, for increasing the level of CTF was validated using advanced progeny. Shinada et al, (2014) evaluated the effect of pyramiding QTLs for improvement of CTF level using eight possible genotype classes from the 152 F 3 population derived from a cross between Eikei88223 and Suisei. And they detected the increasing of CTF levels in combinations between qCTF7 and qCTF12 and between qCTF8 and qCTF12.…”
Section: Molecular Basis Of Cold Tolerancementioning
confidence: 99%
“…() have reported the effects of pyramiding QTLs for cold tolerance at the booting stage. Shinada, Iwata, Sato, and Fujino () improved cold tolerance at the fertilization stage by combinations between QTLs qCTF7 and qCTF12 or between qCTF8 and qCTF12 . Endo et al.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kuroki et al (2011) have reported the effects of pyramiding QTLs for cold tolerance at the booting stage. Shinada, Iwata, Sato, and Fujino (2014) improved cold tolerance at the fertilization stage by combinations between QTLs qCTF7 and qCTF12 or between qCTF8 and qCTF12. Endo et al (2016) have reported the pyramiding of qCT-4 and qLTB3, resulting in an increase of~10% in seed fertility of rice exposed to cold-water treatment.…”
Section: Introductionmentioning
confidence: 99%